The Aha, Ha! Moment: A Gestalt Perspective on Audiovisual Humour (Cinéma & Cie. Film and Media Studies Journal, 2022)
In my previous work about film music, I had adopted Gestalt as a theoretical framework to explain the functions and effects of music in film, from a perspective that did not stem from musicology but from film studies. I developed what I call ‘micro/macro configurations’ analysis. In films, music contributes to the overall form with its specific gestalt (the configuration of the musical structures), and such musical gestalt meets the gestalt of some other cinematic device/s. Besides music, any device (light design, colour schemes, dialogue, acting, camerawork, cutting…) has a specific micro-configuration that can fuse with those of the other devices, and it can be analysed in terms of micro/macro-configuration. The product of the fusion of these micro-configurations is a macro-configuration in which the devices create an audiovisual whole that is ‘something else than the sum of its parts’. In this article I apply this Gestalt-inspired analytical approach to audiovisual humour, more specifically to ‘audiovisual puns’, ‘sight gags’, and ‘perceptual pranks’. The bulk of the examples come from the cinema of the Zucker-Abrahams-Zucker trio, whose comedy is largely based on a clash of incongruous micro-configurations, on perceptual accumulation that creates results similar to multistable figures, and even on comical optical illusions. Closing the article is a proposal that links Gestalt to the Release Theories of humour, explaining the laughter engendered by humour as a ‘Aha, Ha! moment’.
Keywords: Gestalt and film; Neoformalism; Zucker-Abrahams-Zucker; Textual Film Analysis